2017
DOI: 10.1093/nar/gkx871
|View full text |Cite
|
Sign up to set email alerts
|

A cell-penetrating antibody inhibits human RAD51 via direct binding

Abstract: RAD51, a key factor in homology-directed repair (HDR), has long been considered an attractive target for cancer therapy, but few specific inhibitors have been found. A cell-penetrating, anti-DNA, lupus autoantibody, 3E10, was previously shown to inhibit HDR, sensitize tumors to radiation, and mediate synthetic lethal killing of BRCA2-deficient cancer cells, effects that were initially attributed to its affinity for DNA. However, as the molecular basis for its ability to inhibit DNA repair, we report that 3E10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…The Glazer group discovered an autoantibody to RAD51 called 3E10 ( 183 ), which was originally identified as an autoantibody associated with lupus and is considered benign to noncancerous cells ( 184 ). 3E10 directly interacts with the N-terminus of RAD51, and this interaction prevents RAD51 from assembling as a filament onto ssDNA ( 183 ).…”
Section: Rad51 As a Therapeutic Target In Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The Glazer group discovered an autoantibody to RAD51 called 3E10 ( 183 ), which was originally identified as an autoantibody associated with lupus and is considered benign to noncancerous cells ( 184 ). 3E10 directly interacts with the N-terminus of RAD51, and this interaction prevents RAD51 from assembling as a filament onto ssDNA ( 183 ).…”
Section: Rad51 As a Therapeutic Target In Cancer Treatmentmentioning
confidence: 99%
“…The Glazer group discovered an autoantibody to RAD51 called 3E10 ( 183 ), which was originally identified as an autoantibody associated with lupus and is considered benign to noncancerous cells ( 184 ). 3E10 directly interacts with the N-terminus of RAD51, and this interaction prevents RAD51 from assembling as a filament onto ssDNA ( 183 ). An expanded role for 3E10 was demonstrated as 3E10 exposure results in increased toxicity in PTEN-deficient glioma and melanoma cancer cells, which already have a significant propensity for DNA damage ( 185 ).…”
Section: Rad51 As a Therapeutic Target In Cancer Treatmentmentioning
confidence: 99%
“…We recently reported that 3E10 inhibits HDR and does so through a physical interaction with RAD51, resulting in a functional RAD51 inhibition [23]. Based on prior work suggesting that PTEN loss causes a reduction in NHEJ, the other major cellular pathway of DNA DSB repair [18], we sought to test the effect of the 3E10 on PTEN deficient cells.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous other pharmacological strategies are being advanced to inhibit DNA repair, and most utilize small molecules. As an alternative, our group has recently discovered that treatment of human cells with the cell-penetrating autoantibody, 3E10, inhibits DNA DSB repair by HDR through a physical interaction between 3E10 and RAD51 [23]. We demonstrated that 3E10 inhibits RAD51 accumulation on ssDNA and RAD51-dependent DNA strand exchange.…”
Section: Introductionmentioning
confidence: 95%
“…Recently described cell penetrating antibodies also operate through a similar mechanism (Pastushok et al, 2019;Turchick et al, 2017Turchick et al, , 2019. Inhibitors that suppress the D-loop activity of RAD51 have also been reported (Budke et al, 2019;Lv et al, 2016), although several optimized versions also exhibit DNAintercalating activity (Budke et al, 2019).…”
Section: Introductionmentioning
confidence: 99%